International Journal of Food Microbiology - International Union of Microbiological Societies; International Union of Microbiological Societies. Committee on Food Microbiology and Hygiene (Amsterdam : Elsevier Science Publishers, 1984)
Access available online from 1995-
Keywords: Food -- Microbiology -- Periodicals; Microbiology; Bacteriology; Food Microbiology -- Periodicals; Lebensmitteltechnologie; Zeitschrift; Online-Publikation.; Lebensmittelmikrobiologie